AB0406 HUMAN PAPILLOMA VIRUS (HPV) VACCINATION SAFETY IN SYSTEMIC LUPUS ERYTHEMATOSUS COHORT - PORTUGUESE UNIVERSITY HOSPITAL SINGLE-CENTER COHORT STUDY. (2nd June 2020) - Sousa Morais, J.; Oliveira, D. G.; Faria, R.; Almeida, A.; Brandão, M.; Marinho, A.; Almeida, I.; Farinha, F.; Vasconcelos, C.
Abstract : Background: Cervical cancer is a potentially preventable consequence of Human Papillomavirus (HPV). HPV vaccination is recommended in most countries for all young women, preferentially before sexual activity begins. In Portugal, HPV vaccination is available in either bivalent (genotypes 6, 18) or tetravalent (6, 11, 16 e 18) vaccines. Both have aluminum as an adjuvant, a substance arguably capable of inducing inflammatory adjuvant syndromes. Systemic Lupus Erythematosus (SLE) mostly afflicts women of childbearing age, the very target population for HPV vaccination. There are conflicting reports in the literature regarding both the efficacy and safety of this vaccine in SLE patients. This question is particularly pressing as HPV infection prevalence seems to be increased in SLE patients. Objectives: To analyze the safety of HPV vaccination in a SLE patient cohort followed at a university hospital. Methods: Retrospective single-center (35 year long, 436 SLE patient cohort) review of all female SLE patients' local and online national records on HPV vaccination and cervical cancer screening. Data on activity (using SLEDAI-2K scoring) and concomitant drug use were reviewed for the two years before and after vaccination date. Results: Of the 463 SLE patients, 420 were women (91%), of which 322 had clinical information about yes/no HPV vaccination. Twenty-seven of the patients (8%) had one of HPV vaccines, but only 13 (4%) had full information on activity before and after vaccination. Mean current age was 33, 8 years and a minimum of 8, 4 years of follow-up after HPV vaccination. Twenty-there (85%) were vaccinated with the tetravalent vaccine. Pre-vaccination mean SLEDAI score of was 5.9: due to arthritis (n= 5; 38, 5%), low complement (n=4; 31%), dsDNA (n=4; 31%); with a medium dose of 10mg prednisolone/day and 265mg/day of hydroxychloroquine. Post-vaccination mean SLEDAI was 5.8: due to arthritis (n=6; 46%), rash (n= 5; 38, 5%) and low complement (n=6; 46%); with a medium dose of 8mg prednisolone/day and 288mg/day of hydroxychloroquine. There was not a difference in organ involvement before and after vaccination, but rash was slightly more prevalent after vaccination. Conclusion: In our population, HPV vaccination didn't significantly change disease activity and organ involvement or mean dose need of prednisolone or hydroxychloroquine. Although it is a small size SLE sample, it suggests that is safe to administer HPV vaccination to SLE patients. References: [1]eularSegal Yahel, Zabludowicz Center for Autoimmune Diseases, Tel Aviv (2017), "HPV and systemic lupus erythematosus: a mosai of potential crossreaction", SLE Research and Clinical Update, 23 January 2017 [2]Geier David Institute of Chronic Illnesses, USA, (2016), "Quadrivalent human pappilomavirus vaccine and autoimmune adverse events: a case-control assessment of the vaccine adverse event reporting system (VAERS) database, Environment and Autoimmunity, 13 July 2016 Disclosure of Interests: None declared